2003
DOI: 10.1038/sj.npp.1300013
|View full text |Cite
|
Sign up to set email alerts
|

Group II Metabotropic Glutamate Receptor Modulation of DOI-induced c-fos mRNA and Excitatory Responses in the Cerebral Cortex

Abstract: Recent studies have demonstrated that the hallucinogen 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI) enhances glutamatergic transmission in the prefrontal cortex. This increase can be suppressed by metabotropic glutamate2/3 (mGlu2/3) receptor activation. In addition to enhancing glutamatergic transmission, DOI increases cortical c-fos expression. We tested if a reduction in glutamate release produced by mGlu2/3 receptor activation attenuates DOI-induced c-fos expression in the cortex. Similar to previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 28 publications
4
46
1
Order By: Relevance
“…These behaviors, one an operant response and the other, a simple reflex, likely reflect distinct neuroanatomical circuitry, which may be differentially regulated by mGlu2/3 receptors. Such a dichotomy has previously been observed in our laboratory (Benneyworth et al, 2007), as well as others (Zhai et al, 2003), showing that hallucinogen-induced immediate early gene expression is regulated by mGlu2/3 receptors in the mPFC, but not the somatosensory cortex. These experiments may also suggest that these two commonly studied behavioral assays are perhaps modeling distinct aspects of the range of psychological effects of hallucinogens.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These behaviors, one an operant response and the other, a simple reflex, likely reflect distinct neuroanatomical circuitry, which may be differentially regulated by mGlu2/3 receptors. Such a dichotomy has previously been observed in our laboratory (Benneyworth et al, 2007), as well as others (Zhai et al, 2003), showing that hallucinogen-induced immediate early gene expression is regulated by mGlu2/3 receptors in the mPFC, but not the somatosensory cortex. These experiments may also suggest that these two commonly studied behavioral assays are perhaps modeling distinct aspects of the range of psychological effects of hallucinogens.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to the activation of excitatory neurotransmission in brain slices (for review see Aghajanian and Marek, 2000), in vivo neurochemical experiments and ex vivo evaluation of hallucinogen-induced immediate early gene expression support the activation of glutamatergic signaling by hallucinogens (Scruggs et al, 2000(Scruggs et al, , 2003Zhai et al, 2003;Pei et al, 2004;Muschamp et al, 2004). Consistent with this model, group II mGlu receptor agonists have been reported to attenuate the behavioral effects of hallucinogens (Gewirtz and Marek, Drug-naive (panels a and b) and (À)-DOB discrimination-trained mice (panels c and d) were administered LY379268 (3.0 or 10.0 mg/kg) or saline followed by an injection of PCP (5.6 mg/kg) at t ¼ 30 (n ¼ 6-8 per dose).…”
Section: Discussionmentioning
confidence: 99%
“…At least under the conditions described by Gonzá lez-Maeso et al (2008), activation of mGlu2 receptors fails to affect the canonical signaling pathway activated by 5-HT 2A receptors [i.e., the G q -dependent activation of polyphosphoinositide (PI) hydrolysis], which leads to an increased formation of inositol-1,4,5-trisphosphate and diacylglycerol and ultimately to c-Fos induction. These findings, however, are not in agreement with the evidence that the mGlu2/3 receptor agonist LY379268 or the selective mGlu2 receptor enhancer biphenyl-indanone A prevents the induction of c-fos by hallucinogens in the medial prefrontal cortex (Zhai et al, 2003;Benneyworth et al, 2007). Thus, the nature of the interaction between mGlu2/3 and 5-HT 2A is complex, and the detection of immediate early genes as downstream readout systems of receptor activation may be misleading, although it may be advantageous for in vivo studies.…”
Section: N-(4ј-cyano-biphenyl-3-yl)-n-(3-pyridinylmethyl)-ethanesulfon-contrasting
confidence: 55%
“…These findings suggested that mGlu2/3 receptors negatively regulate the ability of 5-HT 2A receptors to stimulate release from thalamic fibers afferent to the prefrontal cortex (Marek et al, 2001). Pharmacological activation of mGlu2/3 receptors has been shown to inhibit the behavioral and electrophysiological effects of hallucinogens (Gewirtz and Marek, 2000;Kłodzinska et al, 2002;Zhai et al, 2003;Winter et al, 2004;Benneyworth et al, 2007) and to prevent the down-regulation of 5-HT 2A receptors induced by repeated administrations of DOI in the prefrontal cortex (Marek et al, 2006). Recent evidence sheds light onto the molecular nature of the interaction between 5-HT 2A and mGlu2/3 receptors.…”
Section: N-(4ј-cyano-biphenyl-3-yl)-n-(3-pyridinylmethyl)-ethanesulfon-mentioning
confidence: 98%
“…The mGluRs are a family of type III G-protein-coupled receptors activated by the excitatory amino acid neurotransmitter Glu, and classified into three major subtypes (group I, mGluR1 and 5 isoforms; group II, mGluR2 and 3 isoforms; group III, mGluR4, 6, 7 and 8 isoforms) based on sequence homology, signal transduction pathway and pharmacology (Conn and Pin, 1997;Schoepp et al, 1999;Zhai et al, 2003). The group I mGluR subtype is coupled to stimulatory G q proteins to activate phospholipase C, which catalyzes the production of diacylglycerol and inositol (1,4,5)-trisphosphate (IP 3 ) for subsequent activation of protein kinase C and release of Ca 2+ from intracellular stores, respectively.…”
Section: Introductionmentioning
confidence: 99%